Unemployment and its causes in the Hail region for the year 2021 AD - Alkhalaf, Hanan Ali; Albassam, Ahmad Mohammed (Journal of Humanities & Social Sciences, 2022)
The study seeks to measure the extent of unemployment in Hail region. This study is also concerned with identifying the causes of unemployment, and analyzing the demographic, social, and economic characteristics of the unemployed in Hail region. and This study adopted survey data consisting of (396) questionnaires collected from the unemployed in the study region, distributed among males and females. The form included two parts: the first is information and data on the unemployed, and the second part dealt with the causes of unemployment, and the data were entered and analyzed by SPSS statistical program. In analyzing its data and presenting its results, the study relied on a number of statistical methods such as the correlation coefficient and chi-squared coefficient, in addition to graphs, and the use of maps. Results: The highest unemployment rate is found in Hail city, where it reached 30% of the unemployment percentage in the region, followed by Al-Hayet Governorate with a rate of 16%, as well as the high rate of those affected as a result of the Corona pandemic, as their rate reached 65% of the unemployed. The study recommended the need to continue doubling the efforts made to achieve the goals of 2030 Vision, which stipulates reducing the unemployment rate from 11.6% to 7%, as well as distributing development projects to the cities and villages of Hail region, and reducing their concentration in Hail city.